Epidemiology, Pathophysiology, and Current Treatment Strategies in Stroke - Ahmed, Zubair; Chaudhary, Fihr; Agrawal, Devendra K. (Cardiology and Cardiovascular Medicine, 2024)
Both ischemic and hemorrhagic strokes are critical health issues and the incidence is on the rise. The rapid neurological degeneration that can occur with either type of stroke warrants prompt medical attention. In the article, we critically reviewed the literature examining their incidence, pathophysiology, and present treatment strategies. Clinical trials show conflicting findings, with ischemic strokes accounting for 87% of all strokes. Brain injury following an ischemic stroke results in cell death and necrosis, immune cells being the primary actors in the process of neuroinflammation. In order to develop neuroprotective drugs against ischemic stroke, detailed investigation of glutamate production and metabolism as well as downstream pathways controlled by glutamate receptors provides significant information on the underlying mechanisms. The permeability of the blood-brain barrier and the degradation of glutamine synthase are two potential mechanisms by which peritoneal dialysis accelerates brainto- blood glutamate clearance and thus reduces glutamate levels in the brain after a stroke. Oxidative stress in an ischemic stroke disturbs the oxidant-antioxidant balance, which is particularly problematic for brain cells that are high in polyunsaturated fatty acids. Because of demographic factors like age, sex, race/ethnicity, and socioeconomic status, the incidence and prevalence of stroke differ across people and regions. For rapid diagnosis and treatment decisions, diagnostic imaging tools such as vascular imaging, CT, and MRI are essential. To aid in the recovery and lessen neurological impairments following a stroke, novel avenues of research are under investigation on neuroprotective medications that target inflammation, oxidative stress, and neuronal death.